Shell-regulated discrete chiral gold-core silver-shell nano material and preparation method thereof
By performing specific chemical treatment on gold nanorods and regulating the silver shell, the problem of chiral signal regulation of chiral plasmon nanomaterials is solved, the amplification and inversion of chiral signals is achieved, and its application potential in biosensing and other fields is enhanced.
Patent Information
- Application Number
- CN202510085883.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The prior art is difficult to accurately regulate the chiral signal of chiral plasmon nanomaterials, affecting its application in the fields of biosensing, tumor treatment, etc.
Adsorption and reaction are carried out by adding a specific dose of cetyltrimethylammonium chloride and cysteine to the anisotropic gold nanorod solution, followed by addition of chloroauric acid and ascorbic acid, and centrifugation dispersion to obtain discrete chiral gold nanorods. Then, silver nitrate and ascorbic acid were added to the solution containing chiral gold nanorods, and the reaction was carried out to obtain a discrete chiral gold core and silver shell nanomaterial regulated by shell.
The large-scale regulation of chiral signals of chiral gold nanoparticles is achieved, and the amplification and inversion of chiral signals is achieved by regulating the silver shell, which improves the application value of nanomaterials in surface detection.
Smart Images

Figure CN119870464A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of optically active metal nanoparticles, and relates to a shell-regulated discrete chiral gold core-silver shell nanomaterial and a preparation method thereof. Background Art
[0002] Chirality refers to the property that an object and its mirror image cannot overlap, just like our left and right hands, which look similar but cannot completely overlap. In the microscopic world, many biological molecules, such as proteins and DNA, have chirality. Chiral substances will have different responses to left-handed and right-handed circularly polarized light, and this property is called circular dichroism (CD). Plasmon chirality combines these two properties. When nanomaterials have both plasmon properties and chiral structures, plasmon chiral nanoparticles are formed. These particles not only have the unique optical enhancement effect brought by plasmons, but also because of the chiral structure, they have significantly different responses to circularly polarized light of different rotation directions, greatly enhancing the circular dichroism signal.
[0003] The gold core-silver shell structure has many significant benefits. First, from the perspective of stability, gold has excellent chemical stability. As a core, it can provide a stable support framework for the entire nanoparticle, effectively preventing the particles from undergoing structural damage or chemical changes under different environmental conditions, and helping to maintain the overall integrity of the chiral plasmon nanoparticles. Secondly, in terms of optical properties, silver has excellent optical properties, and its surface plasmon resonance effect is significant, which can produce strong light absorption and scattering. When silver is wrapped around the gold core as a shell, it can not only enhance the plasmon properties of the nanoparticles, but also interact with the chiral structure to further enhance the chiral optical responses such as circular dichroism (CD) and circularly polarized light absorption (CPL). Chiral plasmon nanomaterials have received increasing attention due to their unique optical activity, and have been widely used in many fields such as biosensing, tumor treatment, and photocatalysis. However, how to accurately control the chiral signals of chiral plasmon nanocrystals remains a difficult problem. Summary of the invention
[0004] The purpose of the present invention is to provide a shell-regulated discrete chiral gold core-silver shell nanomaterial and a preparation method thereof to solve the above defects.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The preparation method of shell-regulated discrete chiral gold core-silver shell nanomaterials comprises the following steps:
[0007] (1) adding hexadecyltrimethylammonium chloride and cysteine to an anisotropic gold nanorod solution in sequence, mixing them evenly and adsorbing them, then adding chloroauric acid and ascorbic acid to react, and after the reaction is completed, centrifugally dispersing them to obtain discrete chiral gold nanorods;
[0008] (2) adding hexadecyltrimethylammonium chloride and cysteine to a solution containing the chiral gold nanorods in sequence, mixing them evenly and adsorbing them, then adding silver nitrate and ascorbic acid to react, and centrifuging the resulting product to obtain a discrete chiral gold core-silver shell nanomaterial with shell-regulated optical activity.
[0009] Preferably, in step (1), the concentration of gold nanorods in the anisotropic gold nanorod solution is in the range of 0.5 to 1 mM.
[0010] Preferably, in step (1), the concentration of hexadecyltrimethylammonium chloride used is 20 mM to 40 mM; and the concentration of cysteine is 40 nM to 100 nM.
[0011] Preferably, in step (1), the molar ratio of ascorbic acid to chloroauric acid is (20-40):1.
[0012] Preferably, the centrifugal speed in step (1) is 4000 r / min to 6000 r / min, and the centrifugal time is 5 min to 10 min; the adsorption time in step (1) is 1 hour, and the adsorption temperature is 30°C.
[0013] Preferably, in step (2), the concentration of chiral gold nanorods in the chiral gold nanorod solution is in the range of 0.5 to 1.5 mM.
[0014] Preferably, in step (2), the concentration of hexadecyltrimethylammonium chloride used is 50mM to 100mM, the concentration of cysteine is 1μM to 4μM, the concentration of silver nitrate is 0-300μM, and the concentration of ascorbic acid is 0-3mM.
[0015] Preferably, in step (2), the product is centrifuged at a speed of 4000 r / min to 6000 r / min, and the centrifugation time is 5 min to 10 min; the adsorption time in step (2) is 1 hour, and the adsorption temperature is 30°C; the reaction time in step (2) is 2 hours, and the reaction temperature is 70°C.
[0016] A shell-regulated discrete chiral gold core-silver shell nanomaterial is prepared according to the above-mentioned shell-regulated discrete chiral gold core-silver shell nanomaterial preparation method, comprising a chiral gold core and a chiral silver shell coating the chiral gold core.
[0017] Preferably, the particle size of the chiral gold core is 50-150 nm, and the thickness of the silver shell is 3-30 nm.
[0018] The beneficial effects of the present invention are:
[0019] (1) The method for preparing discrete chiral gold core-silver shell nanomaterials regulated by the shell layer of the present invention is simple and convenient to operate, takes a short time, has low energy consumption, small loss of raw materials, low preparation cost, and good repeatability and reproducibility. Monodisperse intrinsic chiral gold nanoparticles can be prepared, which have very stable chiral plasmon signals that can be controlled over a large range in the visible light region; these controllable monodisperse precious metal nanoparticles are very suitable for enhanced surface detection (such as enhanced surface Raman effect, biological imaging, etc.), and have wide applicability and promotion value.
[0020] (2) The shell-regulated discrete chiral gold core-silver shell nanomaterial preparation method of the present invention not only realizes the chiral signal regulation of chiral gold nanoparticles in a large range, but also realizes the chirality amplification and reversal of chiral gold nanoparticles by regulating the silver shell. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 : Ultraviolet and transmission electron microscopy images of the gold nanorods prepared in Examples 1-6. Figure 1 a is the UV image of gold nanorods, Figure 1 b is the transmission electron microscopy image of gold nanorods.
[0022] Figure 2 : UV, CD and TEM images of the chiral gold nanorods prepared in Examples 1-6. Figure 2 a is the UV and CD images of gold nanorods. Figure 2 b is the transmission electron microscopy image of chiral gold nanorods.
[0023] Figure 3 : UV, CD and g-factor bar graphs of the chiral gold nanorod core chiral silver shell materials prepared in Examples 1-4. Figure 3 ad are the UV CD images of C-LAμ@LAg, C-LAμ@DAg, C-DAμ@LAg, and C-DAμ@DAg, respectively. Figure 3 eh are the g-factor bar graphs of C-LAμ@LAg, C-LAμ@DAg, C-DAμ@LAg, and C-DAμ@DAg respectively.
[0024] Figure 4 : Transmission electron microscopy image of the chiral gold nanorod core chiral silver shell material prepared in Example 1-2. Figure 4 ac is the transmission electron microscope image of C-LAμ, Figure 4 df is the transmission electron microscopy image of C-LAμ@LAg when the silver nitrate content is 20μl. Figure 4 hi is the transmission electron microscopy image of C-LAμ@DAg when the silver nitrate content is 20μl.
[0025] Figure 5 : Ultraviolet CD image of the chiral gold nanorod core achiral silver shell material prepared in Example 5-6. Figure 5 ab are CD diagrams of C-LAμ@Ag and C-DAμ@Ag, Figure 5 cd are the UV images of C-LAμ@Ag and C-DAμ@Ag, respectively. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with the embodiments. It should be noted that these are merely examples and illustrations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should be deemed to fall within the protection scope of the present invention.
[0027] Embodiment 1:
[0028] A method for preparing a chiral gold nanorod core L-cysteine-induced growth chiral silver shell material (C-LAμ@LAg) comprises the following steps:
[0029] (1) Preparation of left-handed chiral gold nanorods with strong chiral response, as follows:
[0030] A gold nanorod solution was prepared, and the specific preparation steps were as follows: 250 μl of a 10 mM chloroauric acid solution and 600 μl of a 10 mM sodium borohydride solution prepared with 0°C ice water were added to 9.75 mL of a 0.1 M CTAB solution, and the gold nanorod seed solution was obtained after reacting at room temperature for two hours; 2 ml of a 10 mM chloroauric acid solution, 40 ml of a 0.1 M hexadecyltrimethylammonium bromide solution, 0.8 mL of a 1 M hydrochloric acid solution, 0.32 ml of a 0.1 M ascorbic acid, and 0.4 ml of a 0.01 M silver nitrate solution were added to a centrifuge tube, and then 15 μl of the seed solution was immediately added thereto, the mixture was shaken evenly, and the reaction was carried out at 30°C for 12 hours to obtain a gold nanorod solution.
[0031] 1 mL of the gold nanorod solution was centrifuged at 8000 r / min for 10 min to separate the gold nanorod precipitate solution; 4 ml of 40 mM hexadecyltrimethylammonium chloride solution, 50 μl of 5 μM L-cysteine solution and 150 μl of 0.01 M chloroauric acid solution were added thereto and mixed evenly; 475 μl of 0.1 M ascorbic acid solution was then added to the mixed solution, followed by deionized water to make the total volume of the mixed solution 5 mL; the mixture was immediately placed in a 30°C water bath for growth for 2 h, and the product was centrifuged at 6000 r / min for 10 min, and the precipitate was redispersed in deionized water to obtain a chiral gold nanorod solution.
[0032] (2) Preparation of C-LAμ@LAg materials with different shell thicknesses, as follows:
[0033] Five groups of comparative tests were conducted. First, 1 ml of the chiral gold nanorod solution prepared in step (1) was taken, 3 ml of 80 mM hexadecyltrimethylammonium chloride solution was added, 6 μl of 1 mM L-cysteine was added, and adsorbed at 30°C for 1 hour. Then 0 μl, 5 μl, 20 μl, 40 μl, and 80 μl of 10 mM silver nitrate solution were added respectively, and 0.1 M ascorbic acid was immediately added in the same volume as the silver nitrate. Then, it was immediately placed in a 70°C water bath for 2 hours of growth. After the product was centrifuged at 6000 r / min for 10 minutes, the precipitate was redispersed in deionized water to obtain C-LAμ@LAg.
[0034] The UV and TEM images of the gold nanorod solution prepared in step (1) are as follows: Figure 1 As shown, Figure 1 a shows that the transverse plasmon resonance peak of the prepared gold nanorods is at 520nm, and the longitudinal plasmon resonance peak is at 720nm. Figure 1 b shows that the prepared gold nanorods are relatively uniform, with a width of 34nm, a length of about 103nm, and an aspect ratio of about 3. The UV, CD spectra and transmission electron microscopy images of the left-handed chiral gold nanorod (C-LAμ) solution prepared in step (1) are shown in FIG. Figure 2 As shown, Figure 2 a shows that the transverse plasmon resonance peak of the prepared chiral gold rod is at 577nm, which is red-shifted relative to the transverse plasmon resonance peak of the gold nanorod. The longitudinal plasmon resonance peak of the chiral gold rod is at 712nm, which is blue-shifted relative to the longitudinal plasmon resonance peak of the gold nanorod. This indicates that gold grows more on both sides of the gold rod, making the aspect ratio of the chiral gold rod smaller than that of the gold nanorod. Figure 2 The transmission electron microscope image of the chiral gold rod b also proves this point. Figure 2 The width of the chiral gold rod in b is about 70nm, the length is about 140nm, and the aspect ratio is about 2. Figure 2The CD spectra in a show that the chiral gold rods induced by left-handed and right-handed cysteine have good optical activity and show very good symmetry. The chiral peaks are at 572nm and 760nm, respectively, which is consistent with the UV spectrum. The UV and CD spectra of C-LAμ@LAg solutions with different shell thicknesses prepared in step (2) are shown in Figure 2. Figure 3 As shown in a, as the silver nitrate content increases, the UV spectrum blue shifts overall, indicating that silver successfully grows on the surface of the chiral gold rod, and the CD begins to reverse, and the chirality is greatly enhanced. When the silver nitrate content is 20 μl, the g factor reaches the maximum. The specific g factor is as follows Figure 3 e. The transmission images of C-LAμ@LAg are shown in 4d-f, which are very uniform. The silver shell grows more at the four corners of the chiral gold rod. The thickness of the silver shell at the four corners is about 10-15nm, and the thickness of the silver shell on the side is 3-7nm. Most chirality reversals are almost caused by a huge change in the shape of the material, but here it can be observed that the shape of C-LAμ@LAg (4d-f) is almost the same as that of C-LAμ (4a-c), which proves that the chirality reversal of C-LAμ@LAg relative to C-LAμ is not caused by shape change, but by the chiral silver shell. When the cysteine in the chiral gold rod core is the same as the cysteine in the chiral silver shell, it will cause chirality reversal.
[0035] Embodiment 2:
[0036] A method for preparing a chiral gold nanorod core grown by L-cysteine induction and a chiral silver shell material induced by D-cysteine (C-LAμ@DAg) comprises the following steps:
[0037] (1) Preparation of left-handed chiral gold nanorods with strong chiral response, as follows:
[0038] A gold nanorod solution was prepared, and the specific preparation steps were as follows: 250 μl of a 10 mM chloroauric acid solution and 600 μl of a 10 mM sodium borohydride solution prepared with 0°C ice water were added to 9.75 mL of a 0.1 M CTAB solution, and the gold nanorod seed solution was obtained after reacting at room temperature for two hours; 2 ml of a 10 mM chloroauric acid solution, 40 ml of a 0.1 M hexadecyltrimethylammonium bromide solution, 0.8 mL of a 1 M hydrochloric acid solution, 0.32 ml of a 0.1 M ascorbic acid, and 0.4 ml of a 0.01 M silver nitrate solution were added to a centrifuge tube, and then 15 μl of the seed solution was immediately added thereto, the mixture was shaken evenly, and the reaction was carried out at 30°C for 12 hours to obtain a gold nanorod solution.
[0039] 1 mL of the gold nanorod solution was centrifuged at 8000 r / min for 10 min to separate the gold nanorod precipitate solution; 4 ml of 40 mM hexadecyltrimethylammonium chloride solution, 50 μl of 5 μM L-cysteine solution and 150 μl of 0.01 M chloroauric acid solution were added thereto and mixed evenly; 475 μl of 0.1 M ascorbic acid solution was then added to the mixed solution, followed by deionized water to make the total volume of the mixed solution 5 mL; the mixture was immediately placed in a 30°C water bath for growth for 2 h, and the product was centrifuged at 6000 r / min for 10 min, and the precipitate was redispersed in deionized water to obtain a chiral gold nanorod solution.
[0040] (2) Preparation of C-LAμ@DAg materials with different shell thicknesses, as follows:
[0041] Five groups of comparative tests were conducted. First, 1 ml of the chiral gold nanorod solution prepared in step (1) was taken, 3 ml of 80 mM hexadecyltrimethylammonium chloride solution was added, 6 μl of 1 mM dextrorotatory cysteine was added, and adsorbed at 30°C for 1 hour. Then 0 μl, 5 μl, 20 μl, 40 μl, and 80 μl of 10 mM silver nitrate solution were added respectively, and 0.1 M ascorbic acid was immediately added in the same volume as the silver nitrate. Then, it was immediately placed in a 70°C water bath for 2 hours of growth. After the product was centrifuged at 6000 r / min for 10 minutes, the precipitate was redispersed in deionized water to obtain C-LAμ@DAg.
[0042] The UV and TEM images of the gold nanorod solution prepared in step (1) are as follows: Figure 1 As shown, Figure 1 a shows that the transverse plasmon resonance peak of the prepared gold nanorods is at 520nm, and the longitudinal plasmon resonance peak is at 720nm. Figure 1 b shows that the prepared gold nanorods are relatively uniform, with a width of 34nm, a length of about 103nm, and an aspect ratio of about 3. The UV, CD spectra and transmission electron microscopy images of the left-handed chiral gold nanorod (C-LAμ) solution prepared in step (1) are shown in FIG. Figure 2 As shown, Figure 2 a shows that the transverse plasmon resonance peak of the prepared chiral gold rod is at 577nm, which is red-shifted relative to the transverse plasmon resonance peak of the gold nanorod. The longitudinal plasmon resonance peak of the chiral gold rod is at 712nm, which is blue-shifted relative to the longitudinal plasmon resonance peak of the gold nanorod. This indicates that gold grows more on both sides of the gold rod, making the aspect ratio of the chiral gold rod smaller than that of the gold nanorod. Figure 2 The transmission electron microscope image of the chiral gold rod b also proves this point. Figure 2 The width of the chiral gold rod in b is about 70nm, the length is about 140nm, and the aspect ratio is about 2. Figure 2The CD spectra in a show that the chiral gold rods induced by left-handed and right-handed cysteine have good optical activity and show very good symmetry. The chiral peaks are at 572nm and 760nm, respectively, which is consistent with the UV spectrum. The UV and CD spectra of C-LAμ@DAg solutions with different shell thicknesses prepared in step (2) are shown in Figure 2. Figure 3 As shown in b, as the silver nitrate content increases, the UV spectrum blue shifts overall, indicating that silver successfully grows on the surface of the chiral gold rod, CD does not reverse, and the chirality is greatly enhanced. When the silver nitrate content is 20 μl, the g factor reaches the maximum. The specific g factor is as follows Figure 3 f. The transmission image of C-LAμ@DAg is shown in 4g-i, which is very uniform. The silver shell grows more at the four corners of the chiral gold rod. The thickness of the silver shell in the four corners is about 10-15nm, and the thickness of the silver shell on the side is 3-7nm. It can be observed here that the shape of C-LAμ@DAg (4g-i) is almost the same as that of C-LAμ (4a-c) and C-LAμ@LAg (4d-f). When the cysteine in the chiral gold rod core is opposite to the cysteine in the chiral silver shell, it does not lead to chirality reversal.
[0043] Embodiment 3:
[0044] A method for preparing a chiral gold nanorod core L-cysteine-induced chiral silver shell material (C-DAμ@LAg) grown by D-cysteine-induced growth comprises the following steps:
[0045] (1) Preparation of right-handed chiral gold nanorods with strong chiral response, as follows:
[0046] A gold nanorod solution was prepared, and the specific preparation steps were as follows: 250 μl of a 10 mM chloroauric acid solution and 600 μl of a 10 mM sodium borohydride solution prepared with 0°C ice water were added to 9.75 mL of a 0.1 M CTAB solution, and the gold nanorod seed solution was obtained after reacting at room temperature for two hours; 2 ml of a 10 mM chloroauric acid solution, 40 ml of a 0.1 M hexadecyltrimethylammonium bromide solution, 0.8 mL of a 1 M hydrochloric acid solution, 0.32 ml of a 0.1 M ascorbic acid, and 0.4 ml of a 0.01 M silver nitrate solution were added to a centrifuge tube, and then 15 μl of the seed solution was immediately added thereto, the mixture was shaken evenly, and the reaction was carried out at 30°C for 12 hours to obtain a gold nanorod solution.
[0047] 1 mL of the gold nanorod solution was centrifuged at 8000 r / min for 10 min to separate the gold nanorod precipitate solution; 4 ml of 40 mM hexadecyltrimethylammonium chloride solution, 50 μl of 5 μM dextrorotatory cysteine solution and 150 μl of 0.01 M chloroauric acid solution were added thereto and mixed evenly; 475 μl of 0.1 M ascorbic acid solution was then added to the mixed solution, followed by deionized water to make the total volume of the mixed solution 5 mL; the mixture was immediately placed in a 30°C water bath for 2 h, and the product was centrifuged at 6000 r / min for 10 min, and the precipitate was redispersed in deionized water to obtain a chiral gold nanorod solution.
[0048] (2) Preparation of C-DAμ@LAg materials with different shell thicknesses, as follows:
[0049] Five groups of comparative tests were conducted. First, 1 ml of the chiral gold nanorod solution prepared in step (1) was taken, 3 ml of 80 mM hexadecyltrimethylammonium chloride solution was added, 6 μl of 1 mM L-cysteine was added, and adsorbed at 30°C for 1 hour. Then 0 μl, 5 μl, 20 μl, 40 μl, and 80 μl of 10 mM silver nitrate solution were added respectively, and 0.1 M ascorbic acid was immediately added in the same volume as the silver nitrate. Then, it was immediately placed in a 70°C water bath for 2 hours of growth. After the product was centrifuged at 6000 r / min for 10 minutes, the precipitate was redispersed in deionized water to obtain C-DAμ@LAg.
[0050] The UV and TEM images of the gold nanorod solution prepared in step (1) are as follows: Figure 1 As shown, Figure 1 a shows that the transverse plasmon resonance peak of the prepared gold nanorods is at 520nm, and the longitudinal plasmon resonance peak is at 720nm. Figure 1 b shows that the prepared gold nanorods are relatively uniform, with a width of 34 nm, a length of about 103 nm, and an aspect ratio of about 3. The UV and CD spectra of the right-handed chiral gold nanorod (C-DAμ) solution prepared in step (1) are as follows: Figure 2 As shown, Figure 2 a shows that the transverse plasmon resonance peak of the prepared chiral gold rod is at 577nm, which is red-shifted relative to the transverse plasmon resonance peak of the gold nanorod. The longitudinal plasmon resonance peak of the chiral gold rod is at 712nm, which is blue-shifted relative to the longitudinal plasmon resonance peak of the gold nanorod. This indicates that gold grows more on both sides of the gold rod, making the aspect ratio of the chiral gold rod smaller than that of the gold nanorod. Figure 2The CD spectra in a show that the chiral gold rods induced by left-handed and right-handed cysteine have good optical activity and show very good symmetry. The chiral peaks are at 572nm and 760nm, respectively, which is consistent with the UV spectrum. The UV and CD spectra of the C-DAμ@LAg solutions with different shell thicknesses prepared in step (2) are shown in Figure 2. Figure 3 As shown in c, as the silver nitrate content increases, the UV spectrum blue shifts overall, indicating that silver successfully grows on the surface of the chiral gold rod, CD does not reverse, and the chirality is greatly enhanced. When the silver nitrate content is 20 μl, the g factor reaches the maximum. The specific g factor is as follows Figure 3 g. When the cysteine in the chiral gold rod core is opposite to the cysteine in the chiral silver shell, it does not lead to chirality reversal.
[0051] Embodiment 4:
[0052] A method for preparing a chiral gold nanorod core and a chiral silver shell material induced by dextrorotatory cysteine (C-DAμ@DAg) comprising the following steps:
[0053] (1) Preparation of right-handed chiral gold nanorods with strong chiral response, as follows:
[0054] A gold nanorod solution was prepared, and the specific preparation steps were as follows: 250 μl of a 10 mM chloroauric acid solution and 600 μl of a 10 mM sodium borohydride solution prepared with 0°C ice water were added to 9.75 mL of a 0.1 M CTAB solution, and the gold nanorod seed solution was obtained after reacting at room temperature for two hours; 2 ml of a 10 mM chloroauric acid solution, 40 ml of a 0.1 M hexadecyltrimethylammonium bromide solution, 0.8 mL of a 1 M hydrochloric acid solution, 0.32 ml of a 0.1 M ascorbic acid, and 0.4 ml of a 0.01 M silver nitrate solution were added to a centrifuge tube, and then 15 μl of the seed solution was immediately added thereto, the mixture was shaken evenly, and the reaction was carried out at 30°C for 12 hours to obtain a gold nanorod solution.
[0055] 1 mL of the gold nanorod solution was centrifuged at 8000 r / min for 10 min to separate the gold nanorod precipitate solution; 4 ml of 40 mM hexadecyltrimethylammonium chloride solution, 50 μl of 5 μM dextrorotatory cysteine solution and 150 μl of 0.01 M chloroauric acid solution were added thereto and mixed evenly; 475 μl of 0.1 M ascorbic acid solution was then added to the mixed solution, followed by deionized water to make the total volume of the mixed solution 5 mL; the mixture was immediately placed in a 30°C water bath for 2 h, and the product was centrifuged at 6000 r / min for 10 min, and the precipitate was redispersed in deionized water to obtain a chiral gold nanorod solution.
[0056] (2) Preparation of C-DAμ@DAg materials with different shell thicknesses, as follows:
[0057] Five groups of comparative tests were conducted. First, 1 ml of the chiral gold nanorod solution prepared in step (1) was taken, 3 ml of 80 mM hexadecyltrimethylammonium chloride solution was added, 6 μl of 1 mM dextrorotatory cysteine was added, and adsorbed at 30°C for 1 hour. Then 0 μl, 5 μl, 20 μl, 40 μl, and 80 μl of 10 mM silver nitrate solution were added respectively, and 0.1 M ascorbic acid was immediately added in the same volume as the silver nitrate. Then, it was immediately placed in a 70°C water bath for 2 hours of growth. After the product was centrifuged at 6000 r / min for 10 minutes, the precipitate was redispersed in deionized water to obtain C-DAμ@DAg.
[0058] The UV and TEM images of the gold nanorod solution prepared in step (1) are as follows: Figure 1 As shown, Figure 1 a shows that the transverse plasmon resonance peak of the prepared gold nanorods is at 520nm, and the longitudinal plasmon resonance peak is at 720nm. Figure 1 b shows that the prepared gold nanorods are relatively uniform, with a width of 34 nm, a length of about 103 nm, and an aspect ratio of about 3. The UV and CD spectra of the right-handed chiral gold nanorod (C-DAμ) solution prepared in step (1) are as follows: Figure 2 As shown, Figure 2 a shows that the transverse plasmon resonance peak of the prepared chiral gold rod is at 577nm, which is red-shifted relative to the transverse plasmon resonance peak of the gold nanorod. The longitudinal plasmon resonance peak of the chiral gold rod is at 712nm, which is blue-shifted relative to the longitudinal plasmon resonance peak of the gold nanorod. This indicates that gold grows more on both sides of the gold rod, making the aspect ratio of the chiral gold rod smaller than that of the gold nanorod. Figure 2 The CD spectra in a show that the chiral gold rods induced by left-handed and right-handed cysteine have good optical activity and show very good symmetry. The chiral peaks are at 572nm and 760nm, respectively, which is consistent with the UV spectrum. The UV and CD spectra of C-DAμ@DAg solutions with different shell thicknesses prepared in step (2) are shown in Figure 2. Figure 3 As shown in d, as the silver nitrate content increases, the UV spectrum blue shifts overall, indicating that silver successfully grows on the surface of the chiral gold rod, CD is reversed, and the chirality is greatly enhanced. When the silver nitrate content is 20 μl, the g factor reaches the maximum. The specific g factor is as follows Figure 3 h. When the cysteine in the chiral gold rod core is the same as the cysteine in the chiral silver shell, the chirality is reversed.
[0059] Embodiment 5:
[0060] A method for preparing a chiral gold nanorod core achiral silver shell material (C-LAμ@Ag) induced by L-cysteine growth comprises the following steps:
[0061] (1) Preparation of left-handed chiral gold nanorods with strong chiral response, as follows:
[0062] A gold nanorod solution was prepared, and the specific preparation steps were as follows: 250 μl of a 10 mM chloroauric acid solution and 600 μl of a 10 mM sodium borohydride solution prepared with 0°C ice water were added to 9.75 mL of a 0.1 M CTAB solution, and the gold nanorod seed solution was obtained after reacting at room temperature for two hours; 2 ml of a 10 mM chloroauric acid solution, 40 ml of a 0.1 M hexadecyltrimethylammonium bromide solution, 0.8 mL of a 1 M hydrochloric acid solution, 0.32 ml of a 0.1 M ascorbic acid, and 0.4 ml of a 0.01 M silver nitrate solution were added to a centrifuge tube, and then 15 μl of the seed solution was immediately added thereto, the mixture was shaken evenly, and the reaction was carried out at 30°C for 12 hours to obtain a gold nanorod solution.
[0063] 1 mL of the gold nanorod solution was centrifuged at 8000 r / min for 10 min to separate the gold nanorod precipitate solution; 4 ml of 40 mM hexadecyltrimethylammonium chloride solution, 50 μl of 5 μM L-cysteine solution and 150 μl of 0.01 M chloroauric acid solution were added thereto and mixed evenly; 475 μl of 0.1 M ascorbic acid solution was then added to the mixed solution, followed by deionized water to make the total volume of the mixed solution 5 mL; the mixture was immediately placed in a 30°C water bath for growth for 2 h, and the product was centrifuged at 6000 r / min for 10 min, and the precipitate was redispersed in deionized water to obtain a chiral gold nanorod solution.
[0064] (2) Preparation of C-LAμ@Ag materials with different shell thicknesses, as follows:
[0065] Five groups of comparative tests were conducted. First, 1 ml of the chiral gold nanorod solution prepared in step (1) was taken, 3 ml of 80 mM hexadecyltrimethylammonium chloride solution was added, and 0 μl, 5 μl, 20 μl, 40 μl, and 80 μl of 10 mM silver nitrate solution were added respectively, and 0.1 M ascorbic acid was immediately added at the same volume as the silver nitrate. Then, the mixture was immediately placed in a 70°C water bath for 4 h. After the product was centrifuged at 6000 r / min for 10 min, the precipitate was redispersed in deionized water to obtain C-LAμ@Ag.
[0066] The UV and TEM images of the gold nanorod solution prepared in step (1) are as follows: Figure 1 As shown, Figure 1a shows that the transverse plasmon resonance peak of the prepared gold nanorods is at 520nm, and the longitudinal plasmon resonance peak is at 720nm. Figure 1 b shows that the prepared gold nanorods are relatively uniform, with a width of 34nm, a length of about 103nm, and an aspect ratio of about 3. The UV, CD spectra and transmission electron microscopy images of the left-handed chiral gold nanorod (C-LAμ) solution prepared in step (1) are shown in FIG. Figure 2 As shown, Figure 2 a shows that the transverse plasmon resonance peak of the prepared chiral gold rod is at 577nm, which is red-shifted relative to the transverse plasmon resonance peak of the gold nanorod. The longitudinal plasmon resonance peak of the chiral gold rod is at 712nm, which is blue-shifted relative to the longitudinal plasmon resonance peak of the gold nanorod. This indicates that gold grows more on both sides of the gold rod, making the aspect ratio of the chiral gold rod smaller than that of the gold nanorod. Figure 2 The transmission electron microscope image of the chiral gold rod b also proves this point. Figure 2 The width of the chiral gold rod in b is about 70nm, the length is about 140nm, and the aspect ratio is about 2. Figure 2 The CD spectra in a show that the chiral gold rods induced by left-handed and right-handed cysteine have good optical activity and show very good symmetry. The chiral peaks are at 572nm and 760nm, respectively, which is consistent with the UV spectrum. The UV and CD spectra of C-LAμ@Ag solutions with different shell thicknesses prepared in step (2) are shown in Figure 2. Figure 5 As shown in Figure 5a, as the silver nitrate content increases, the UV spectrum blue-shifts overall, but the gold chirality gradually disappears, and a weak silver chirality peak begins to appear. This indicates that the silver shell cannot lead to chirality amplification and reversal, and the real effect is the cysteine in the silver shell.
[0067] Embodiment 6:
[0068] A method for preparing a chiral gold nanorod core achiral silver shell material (C-DAμ@Ag) induced by dextrorotatory cysteine growth comprises the following steps:
[0069] (1) Preparation of right-handed chiral gold nanorods with strong chiral response, as follows:
[0070] A gold nanorod solution was prepared, and the specific preparation steps were as follows: 250 μl of a 10 mM chloroauric acid solution and 600 μl of a 10 mM sodium borohydride solution prepared with 0°C ice water were added to 9.75 mL of a 0.1 M CTAB solution, and the gold nanorod seed solution was obtained after reacting at room temperature for two hours; 2 ml of a 10 mM chloroauric acid solution, 40 ml of a 0.1 M hexadecyltrimethylammonium bromide solution, 0.8 mL of a 1 M hydrochloric acid solution, 0.32 ml of a 0.1 M ascorbic acid, and 0.4 ml of a 0.01 M silver nitrate solution were added to a centrifuge tube, and then 15 μl of the seed solution was immediately added thereto, the mixture was shaken evenly, and the reaction was carried out at 30°C for 12 hours to obtain a gold nanorod solution.
[0071] 1 mL of the gold nanorod solution was centrifuged at 8000 r / min for 10 min to separate the gold nanorod precipitate solution; 4 ml of 40 mM hexadecyltrimethylammonium chloride solution, 50 μl of 5 μM dextrorotatory cysteine solution and 150 μl of 0.01 M chloroauric acid solution were added thereto and mixed evenly; 475 μl of 0.1 M ascorbic acid solution was then added to the mixed solution, followed by deionized water to make the total volume of the mixed solution 5 mL; the mixture was immediately placed in a 30°C water bath for 2 h, and the product was centrifuged at 6000 r / min for 10 min, and the precipitate was redispersed in deionized water to obtain a chiral gold nanorod solution.
[0072] (2) Preparation of C-DAμ@Ag materials with different shell thicknesses, as follows:
[0073] Five groups of comparative tests were conducted. First, 1 ml of the chiral gold nanorod solution prepared in step (1) was taken, 3 ml of 80 mM hexadecyltrimethylammonium chloride solution was added, and 0 μl, 5 μl, 20 μl, 40 μl, and 80 μl of 10 mM silver nitrate solution were added respectively, and 0.1 M ascorbic acid was immediately added in the same volume as the silver nitrate. Then, the mixture was immediately placed in a 70°C water bath and grown for 4 h. After the product was centrifuged at 6000 r / min for 10 min, the precipitate was redispersed in deionized water to obtain C-DAμ@Ag.
[0074] The UV and TEM images of the gold nanorod solution prepared in step (1) are as follows: Figure 1 As shown, Figure 1 a shows that the transverse plasmon resonance peak of the prepared gold nanorods is at 520nm, and the longitudinal plasmon resonance peak is at 720nm. Figure 1 b shows that the prepared gold nanorods are relatively uniform, with a width of 34 nm, a length of about 103 nm, and an aspect ratio of about 3. The UV and CD spectra of the right-handed chiral gold nanorod (C-DAμ) solution prepared in step (1) are as follows: Figure 2 As shown, Figure 2 a shows that the transverse plasmon resonance peak of the prepared chiral gold rod is at 577nm, which is red-shifted relative to the transverse plasmon resonance peak of the gold nanorod. The longitudinal plasmon resonance peak of the chiral gold rod is at 712nm, which is blue-shifted relative to the longitudinal plasmon resonance peak of the gold nanorod. This indicates that gold grows more on both sides of the gold rod, making the aspect ratio of the chiral gold rod smaller than that of the gold nanorod. Figure 2 The CD spectra in a show that the chiral gold rods induced by left-handed and right-handed cysteine have good optical activity and show very good symmetry. The chiral peaks are at 572nm and 760nm, respectively, which is consistent with the UV spectrum. The UV and CD spectra of C-DAμ@Ag solutions with different shell thicknesses prepared in step (2) are shown in Figure 2. Figure 5 As shown in Figure 5b, as the silver nitrate content increases, the UV spectrum blue-shifts overall, but the gold chirality gradually disappears, and a weak silver chirality peak begins to appear. This indicates that the silver shell cannot lead to chirality amplification and reversal, and the real effect is the cysteine in the silver shell.
[0075] The results of Examples 1 to 6 are analyzed:
[0076] (1) Properties of L-cysteine-induced chiral gold nanorod core and L-cysteine-induced chiral silver shell material (C-LAμ@LAg):
[0077] Figure 3 a shows that the thickness of the chiral silver shell has a great regulatory effect on the chiral gold nanorods. When the cysteine in the gold core and the silver shell is the same, both are L-cysteine, as the thickness of the silver shell increases, the plasmon resonance peak gradually blue-shifts, and as the thickness of the chiral silver shell continues to increase, the UV continues to blue-shift, the CD begins to reverse, and the chirality is greatly enhanced. When the amount of silver nitrate is 20μl, the g factor reaches the maximum, and the positive and negative values are opposite to those of the initial g factor of the chiral gold nanorod core. Figure 4 df shows that the silver shell grows more at the four corners of the chiral gold rod. The thickness of the silver shell at the four corners is about 10-15nm, and the thickness of the silver shell on the side is 3-7nm. As the thickness of the silver shell increases further, the chirality of gold begins to weaken and the chiral peak of silver begins to appear.
[0078] (2) Properties of chiral gold nanorod cores induced by L-cysteine and chiral silver shells induced by D-cysteine (C-LAμ@DAg):
[0079] Figure 3b shows that the thickness of the chiral silver shell has a great regulatory effect on the chiral gold nanorods. When the cysteine in the gold core and the silver shell is opposite, as the thickness of the silver shell increases, the plasmon resonance peak gradually blue-shifts. As the thickness of the chiral silver shell continues to increase, the UV continues to blue-shift, but the CD does not reverse, and the chirality is greatly enhanced. When the amount of silver nitrate is 20μl, the g factor reaches the maximum, and the positive and negative values are the same as those of the initial chiral gold nanorod core. Figure 4 gi shows that the silver shell grows more at the four corners of the chiral gold rod. The thickness of the silver shell in the four corners is about 10-15nm, and the thickness of the silver shell on the side is 3-7nm. As the thickness of the silver shell increases further, the chirality of gold begins to weaken and the chiral peak of silver begins to appear.
[0080] (3) Property analysis of chiral gold nanorod core induced by D-cysteine and chiral silver shell induced by L-cysteine (C-DAμ@LAg):
[0081] Figure 3 c shows that the thickness of the chiral silver shell has a great regulatory effect on the chiral gold nanorods. When the cysteine in the gold core and the silver shell are opposite, as the thickness of the silver shell increases, the plasmon resonance peak gradually blue-shifts. As the thickness of the chiral silver shell continues to increase, the UV continues to blue-shift, but the CD does not reverse, and the chirality is greatly enhanced. When the amount of silver nitrate is 20μl, the g factor reaches the maximum, and the positive and negative values are the same as those of the initial chiral gold nanorod core. As the thickness of the silver shell increases further, the chirality of gold begins to weaken, and the chiral peak of silver begins to appear.
[0082] (4) Properties of chiral gold nanorod core induced by D-cysteine and chiral silver shell material induced by D-cysteine (C-DAμ@DAg):
[0083] Figure 3 d shows that the thickness of the chiral silver shell has a great regulatory effect on the chiral gold nanorods. When the cysteine in the gold core and the silver shell is the same, both are right-handed cysteine, as the thickness of the silver shell increases, the plasmon resonance peak gradually blue-shifts. As the thickness of the chiral silver shell continues to increase, the UV continues to blue-shift, the CD begins to reverse, and the chirality is greatly enhanced. When the amount of silver nitrate is 20μl, the g factor reaches the maximum, and the positive and negative values are opposite to those of the initial chiral gold nanorod core. As the thickness of the silver shell increases further, the chirality of gold begins to weaken, and the chiral peak of silver begins to appear.
[0084] (5) Properties of chiral gold nanorod core achiral silver shell material (C-LAμ@Ag) induced by L-cysteine:
[0085] Figure 5a shows that the thickness of the achiral silver shell has a great regulatory effect on the chiral gold nanorods. When there is no cysteine in the silver shell, as the silver shell increases, the ultraviolet continues to blue shift, and the chirality of gold begins to weaken. As the silver shell increases further, the chiral peak of gold almost completely disappears, but a weak chiral peak of silver begins to appear.
[0086] (6) Properties of chiral gold nanorod core achiral silver shell material (C-DAμ@Ag) induced by dextrorotatory cysteine:
[0087] Figure 5 b shows that the thickness of the achiral silver shell has a great regulatory effect on the chiral gold nanorods. When there is no cysteine in the silver shell, as the silver shell increases, the ultraviolet continues to blue shift, and the chirality of gold begins to weaken. As the silver shell increases further, the chiral peak of gold almost completely disappears, but a weak chiral peak of silver begins to appear.
[0088] The shell-regulated discrete chiral gold core-silver shell nanomaterial preparation method of the present invention is simple and convenient to operate, short in time, low in energy consumption, small in raw material loss, low in preparation cost, and very good in repeatability and reproducibility. Monodisperse intrinsic chiral gold nanoparticles can be prepared, and the chiral plasmon signals in the visible light region are very stable and controllable over a large range. These controllable monodisperse noble metal nanoparticles are very suitable for enhanced surface detection (such as enhanced surface Raman effect, biological imaging, etc.), and have wide applicability and promotion value.
[0089] The shell-regulated discrete chiral gold core-silver shell nanomaterial preparation method of the present invention not only realizes the chiral signal regulation of chiral gold nanoparticles in a large range, but also realizes the chirality amplification and reversal of chiral gold nanoparticles by regulating the silver shell.
[0090] In summary, the beneficial effects of the present invention are as follows: (1) The method for preparing discrete chiral gold core-silver shell nanomaterials regulated by the shell layer of the present invention is simple and convenient to operate, takes a short time, has low energy consumption, has low raw material loss, has low preparation cost, and has good repeatability and reproducibility. Monodisperse intrinsic chiral gold nanoparticles can be prepared, which have very stable chiral plasmon signals that can be controlled over a large range in the visible light region; these controllable monodisperse precious metal nanoparticles are very suitable for enhancing surface detection (such as enhancing surface Raman effect, bioimaging, etc.), and have wide applicability and promotion value. (2) The method for preparing discrete chiral gold core-silver shell nanomaterials regulated by the shell layer of the present invention not only realizes the chiral signal of chiral gold nanoparticles regulated over a large range, but also realizes the chirality amplification and reversal of chiral gold nanoparticles by regulating the silver shell.
[0091] The above embodiments are typical embodiments of the present invention and are not intended to limit the present invention in any way. Therefore, according to the overall concept of the present invention, any adjustment or modification of the process parameters described by a person skilled in the art shall fall within the protection scope of the present invention as long as it does not deviate from the concept of the invention or exceed the scope defined in the claims.
Claims
1. A method for preparing a shell-regulated discrete chiral gold core-silver shell nanomaterial, characterized in that: The steps include: (1) adding hexadecyltrimethylammonium chloride and cysteine to an anisotropic gold nanorod solution in sequence, mixing them evenly and adsorbing them, then adding chloroauric acid and ascorbic acid to react, and after the reaction is completed, centrifugally dispersing them to obtain discrete chiral gold nanorods; (2) adding hexadecyltrimethylammonium chloride and cysteine to a solution containing the chiral gold nanorods in sequence, mixing them evenly and adsorbing them, then adding silver nitrate and ascorbic acid to react, and centrifuging the resulting product to obtain a discrete chiral gold core-silver shell nanomaterial with shell-regulated optical activity.
2. The preparation method according to claim 1, characterized in that: In the step (1), the concentration of gold nanorods in the anisotropic gold nanorod solution is in the range of 0.5 to 1 mM.
3. The preparation method according to claim 1, characterized in that: In the step (1), the concentration of hexadecyltrimethylammonium chloride is 20 mM to 40 mM; the concentration of cysteine is 40 nM to 100 nM.
4. The preparation method according to claim 1, characterized in that: In the step (1), the molar ratio of ascorbic acid to chloroauric acid is (20-40):
1.
5. The preparation method according to claim 1, characterized in that: The centrifugal speed in step (1) is 4000 r / min to 6000 r / min, and the centrifugal time is 5 min to 10 min; the adsorption time in step (1) is 1 hour, and the adsorption temperature is 30°C.
6. The preparation method according to claim 1, characterized in that: In the step (2), the concentration of the chiral gold nanorods in the chiral gold nanorod solution is in the range of 0.5 to 1.5 mM.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In the step (2), the concentration of hexadecyltrimethylammonium chloride used is 50mM to 100mM, the concentration of cysteine is 1μM to 4μM, the concentration of silver nitrate is 0-300μM, and the concentration of ascorbic acid is 0-3mM.
8. The preparation method according to claim 7, characterized in that: In the step (2), the product is centrifuged at a speed of 4000 r / min to 6000 r / min, and the centrifugation time is 5 min to 10 min; the adsorption time in the step (2) is 1 hour, and the adsorption temperature is 30° C.; the reaction time in the step (2) is 2 hours, and the reaction temperature is 70° C.
9. A shell-regulated discrete chiral gold core-silver shell nanomaterial, characterized in that: The material is prepared according to the method for preparing a shell-regulated discrete chiral gold core-silver shell nanomaterial according to any one of claims 1 to 8, comprising a chiral gold core and a chiral silver shell coating the chiral gold core.
10. The shell-regulated discrete chiral gold core-silver shell nanomaterial according to claim 9, characterized in that: The particle size of the chiral gold core is 50-150 nm, and the thickness of the silver shell is 3-30 nm.
Citation Information
Patent Citations
Method for promoting regrowth of silver on gold nanosphere surface and application thereof
CN105499560A
Discrete precious metal nanoparticles and preparing method thereof
CN106238728A
Chiral precious metal nano-particle and preparation method and application thereof
CN111112596A
Chiral assembly and preparation method thereof
CN111299569A
Chiral gold-paramagnetic iron trioxide core-shell structure composite material and preparation method thereof
CN118142547A